Limbo in development projects. Issue 7 (3rd October 2019) - Andersen, Lars Bo
ABSTRACT: This article uses Actor-Network Theory to investigate how a One Laptop per Child project went through periods of impasse and crisis, what happened during these periods, and how the project managed to continue. The analysis shows that the standstills occurred when the understandings or "translations" behind the project started to unravel and, similarly, that the project was revitalised by participants experimenting with new translations. The article develops a sensitising concept called limbo intended to guide others confronted with similar situations. The concept has three traits: standstills are circumstantial, they entail ambiguity, and they are sources of project transformation.